Liquid Temperature Dependent Behaviour of a Cavitation Bubble in Acoustic Field - AL-Asady, Abbas Z. (Basrah Journal for Engineering Sciences, 2007)
A new model of bubble dynamics is constructed using linear wave equation, including effects of variation of the gas temperature inside the bubble and the liquid temperature near the bubble, and effects of evaporation-condensation of the liquid vapour at the bubble wall. The liquid is assumed water and the gas inside the bubble is only vapour (neglecting non-condensable gas). The temperature inside the bubble and the liquid temperature are numerically calculated by solving the energy equation both inside (vapour-phase) and outside (liquid-phase) the bubble (using finite difference method). The pressure inside the bubble is obtained numerically without assuming that it follows any assuming relation. The results reveal that the bubble radius, the liquid temperature, and the pressure and temperature inside the bubble change with time periodically. Both the pressure and temperature become higher when the radius becomes minimum. The present theoretical result is compared with data from other reference and with another theoretical model to check the validity of the present model. The calculated result approximately fits with the data of the previous studies.